Clinical evaluation of a multiplex droplet digital PCR for diagnosing suspected bloodstream infections: a prospective study - Yaqin Peng; Ruijie Xie; Yifeng Luo; Yifeng Luo; Yifeng Luo; Penghao Guo; Zhongwen Wu; Yili Chen; Pingjuan Liu; Jiankai Deng; Bin Huang; Kang Liao (Frontiers in Cellular and Infection Microbiology)
BackgroundThough droplet digital PCR (ddPCR) has emerged as a promising tool for early pathogen detection in bloodstream infections (BSIs), more studies are needed to support its clinical application widely due to different ddPCR platforms with discrepant diagnostic performance. Additionally, there is still a lack of clinical data to reveal the association between pathogen loads detected by ddPCR and corresponding BSIs.MethodsIn this prospective study, 173 patients with suspected BSIs were enrolled. A multiplex ddPCR assay was used to detect 18 pathogens. The results of ddPCR testing were evaluated in comparison with blood cultures (BCs) and clinical diagnosis. Taking BC as the gold standard, receiver operating characteristic curve and Cohen’s kappa agreement were used to investigate whether the pathogen load could predict a corresponding culture-proven BSI for the top five microorganisms detected by ddPCR.ResultsOf the 173 blood samples collected, BC and ddPCR were positive in 48 (27.7%) and 92 (53.2%) cases, respectively. Compared to BC, the aggregate sensitivity and specificity for ddPCR were 81.3% and 63.2%, respectively. After clinical adjudication, the sensitivity and specificity of ddPCR increased to 88.8% and 86.0%, respectively. There were 143 microorganisms detected by ddPCR. The DNA loads of these microorganisms ranged from 30.0 to 3.2×105 copies/mL (median level: 158.0 copies/mL), 72.7% (104/143) of which were below 1,000 copies/mL. Further, statistical analysis showed the DNA loads of Escherichia coli (AUC: 0.954, 95% CI: 0.898-1.000, κ=0.731, cut-off values: 93.0 copies/mL) and Klebsiella pneumoniae (AUC: 0.994, 95% CI: 0.986-1.000, κ=0.834, cut-off values: 196.5 copies/mL) were excellent predictors for the corresponding BSIs. The DNA loads of Pseudomonas aeruginosa (AUC: 0.816, 95% CI: 0.560-1.000, κ=0.167), Acinetobacter baumannii (AUC: 0.728, 95% CI: 0.195-1.000), and Enterococcus spp. (AUC: 0.282, 95% CI: 0.000-0.778) had little predictive value for the corresponding culture-proven BSIs.ConclusionOur results indicate that the multiplex ddPCR is a promising platform as a complementary add-on to conventional BC. The DNA loads of E. coli and K. pneumoniae present excellent predictive value for the corresponding BSIs. Further research is needed to explore the predictive potential of ddPCR for other microorganisms.